Isolation, Culture, and Transient Transformation of Plant Protoplasts. Issue 1 (3rd June 2014) - Shen, Jinbo; Fu, Jiaxin; Ma, Jin; Wang, Xiangfeng; Gao, Caiji; Zhuang, ChuXiong; Wan, Jianmin; Jiang, Liwen
Abstract: Transient gene expression in protoplasts, which has been used in several plant species, is an important and versatile tool for rapid functional gene analysis, protein subcellular localization, and biochemical manipulations. This unit describes transient gene expression by electroporation of DNA into protoplasts of Arabidopsis or tobacco suspension‐cultured cells and by polyethylene glycol (PEG)‐mediated DNA transformation into protoplasts derived from rice leaf sheaths. PEG‐mediated DNA transformation for transient gene expression in rice protoplasts in suspension culture is also described as an alternative technique. Methods for collecting intracellular and secreted proteins are also provided. Curr. Protoc. Cell Biol . 63:2.8.1‐2.8.17. © 2014 by John Wiley & Sons, Inc.